Modification Method of Cycloid Tooth Profile based on Pressure Angle - Lang Yue; Weidong He; Yinghui Zhang (Jixie chuandong)
Abrscat For the cycloid gear of RV reducer used in robot， on the basis of the isometric modification method， the modification quantity is changed in linear and polynomial ways， and the cycloid tooth profile equations after profile modification are derived. Based on the change rule of pressure angle， by controlling the maximum pressure angle and the maximum profile modification of tooth root and top， the tooth profile modification at different positions in the modification interval of the tooth profile curve can be controlled. The biggest difference between profile modification method based on the pressure angle and the traditional method is that in the working section of cycloid gear， the tooth profile of cycloid gear is standard， and the non-working section and the working section are smoothly connected. The modification program of cycloid tooth profile is compiled in VB， and modification interval and meshing force are compared under different profile modification and pressure angle. Different pressure angles correspond to different working areas， and the meshing force distribution based on pressure angle sectional modification method is more uniform.